UNIVERSITY NOTES. (The Accounting Review, 1930)
Abstract This article presents information regarding the faculty and admission of various university. In the University of Alabama, T.W. Wood, has gone to Howard College, Brimingham, as instructor in accounting. The School of Business Administration is establishing a Bureau of Business Research with H.H. Chapman as director. Enrollment in accounting courses continues to increase and there are now 45 juniors and seniors majoring in accounting. in the University of Chicago, W.J. Graham has been promoted to the rank of assistant professor. H.C. Daines is serving as a member of the educational committee of the Illinois Society of Certified Public Accountants. In the University of Denver, F.C. Onstott, professor of accounting, and university registrar, is visiting the chief university departments of business in the country to make an intimate study of the accounting curricula of these schools with a view to revising the curriculum at Denver. E.A. Zelliott has been added to the teaching staff in elementary accounting. E.G. Plowman has been appointed head of the work in marketing and director of the bureau of business research.